Mormo na equideocultura brasileira: identificação e caracterização de Burkholderia mallei em equídeos com e sem manifestações clínicas - Paula Adas Pereira Suniga (2024)
Glanders, an infectious disease that predominantly affects equidae (horses, mules and donkeys), is caused by the bacterium Burkholderia mallei, a Gram-negative, non-fermenting and immobile coccobacillus. This zoonosis, which was declared eradicated in Brazil in 1960, re-emerged in the 2000s with the detection of seropositive equids, especially in the northeast region of the country. Equidae, which number 116 million globally and 6.7 million in Brazil, play a crucial role in the economy and people's survival. Maintaining the health of these animals through appropriate health management practices, as recommended by the National Equine Health Program, is essential for the sustainability and profitability of the agricultural sector, in addition to being important for animal welfare. Therefore, the objective of the work was to identify the presence of B. mallei in symptomatic and asymptomatic equids, seeking a broad characterization of Brazilian strains. In this study, we demonstrated the detection of B. mallei in horses seropositive for glanders in all five geographic regions of Brazil using species-specific PCR, directly from tissues or bacterial cultures, followed by amplicon sequencing. This finding expands the possibility of isolating strains and carrying out epidemiological characterizations based on molecular information. Additionally, there was microbiological detection of B. mallei in cultures of nasal and palatal swabs, which suggests the elimination of the agent into the environment. In addition to these, the case of an asymptomatic mare with positive antibody titers to B. mallei was investigated using a multifaceted approach that encompassed microbiological cultivation, mass spectrometry and whole genome sequencing. The strain was identified as B. mallei by PCR and confirmed by MALDI-TOF mass spectrometry. Whole-genome sequencing revealed a genome size of 5.51 Mb with a GC content of 65.8%, 5,871 genes (including 4 rRNA genes and 53 tRNA genes), and 5,583 DNA coding sequences (CDSs). 227 predicted pseudogenes were detected and in silico analysis of different genomic loci allowed the differentiation of the B. mallei isolate from Burkholderia pseudomallei. The BAC 86/19 strain was identified as lineage 3, sub-lineage 2, which includes other strains from Brazil, India and Iran. Genome sequencing of this strain provides relevant data for future research that seeks to improve the diagnosis and potential treatment of this disease , in addition to studies focused on the infectious agent and its epidemiology. In short, the present work contributes significantly to the understanding of the epidemiology of glanders in Brazil, highlighting the importance of detection and molecular characterization of B. mallei for the control and prevention of the disease. Furthermore, the studies highlight the need for continuous surveillance, even in asymptomatic horses. This research reinforces the need for an integrated approach to glanders control as there are significant economic and zoonotic implications.